Mapping the Path to Teacher Performance: Discipline, Emotional Intelligence, and Job Satisfaction - Valentinus Vally; Lianto Lianto (Universitas Nurul Jadid, 2025)
This study aims to analyze the influence of work discipline and emotional intelligence on teacher performance with job satisfaction as a mediating variable. Using a quantitative approach and Structural Equation Modeling analysis with SmartPLS 4.0, data were analyzed from 39 respondents. The results showed that work discipline had a significant effect on job satisfaction (β = 0.771; p < 0.001) and teacher performance (β = 0.538; p < 0.001). In contrast, emotional intelligence did not show a significant effect on job satisfaction (β = 0.038; p = 0.729), but directly affected teacher performance (β = 0.346; p < 0.001). Job satisfaction made a positive contribution to performance (β = 0.315; p = 0.006) and partially mediated the relationship between work discipline and performance (β = 0.242; p = 0.006). This model explains 84.5% of the variance in teacher performance. These findings confirm that work discipline is an important personal resource for improving performance, both directly and by increasing job satisfaction. At the same time, emotional intelligence serves as a direct driver of performance. Practical implications recommend improved discipline, performance-based emotional intelligence training, and improved working conditions to support optimal job satisfaction.